Oxygen deprivation influences the survival of Listeria monocytogenes in gerbils1. Issue 1 (3rd October 2018) - Harris, Jillian; Paul, Oindrila; Park, Si Hong; White, Sally J; Budachetri, Khemraj; McClung, Daniel M; Wilson, Jessica G; Olivier, Alicia K; Thornton, Justin A; Broadway, Paul R; Ricke, Steven C; Donaldson, Janet R
Abstract: Listeria monocytogenes is a facultative anaerobic foodborne pathogen capable of surviving harsh environments. Recent work has indicated that anaerobic conditions increase the resistance capability of certain strains to environmental stressors. The goal of the study was to conduct a preliminary study to determine whether exposure to anaerobic conditions prior to infection increases the ability to survive in vivo. Gerbils were inoculated with one of five doses of the L. monocytogenes strain F2365 by oral gavage: phosphate-buffered saline (control), 5 × 10 6 colony forming units aerobic culture (low aerobic), 5 × 10 8 aerobic culture (high aerobic), 5 × 10 6 anaerobic culture (low anaerobic), or 5 × 10 8 anaerobic culture (high anaerobic) dose of F2365. Gerbils inoculated with a high aerobic or anaerobic dose exhibited significant weight loss. Gerbils administered either the low or high anaerobic dose had at least 3 log10 of L. monocytogenes present in fecal samples, which contrasted with gerbils that received the low aerobic dose. Animals that received the high anaerobic dose had a significant increase in bacterial loads within the liver. Histologic examination of the L. monocytogenes positive livers exhibited locally extensive areas of hepatocellular necrosis, though the extent of this damage differed between treatment groups. Microbial community analysis of the cecum from gerbils infected with L. monocytogenes indicated that the abundance of Bacteroidales and Clostridiales increased and there was a decrease in the abundance of Spirochaetales. This study suggests that anaerobic conditions alter the localization pattern of L. monocytogenes within the gastrointestinal tract. These findings could relate to how different populations are more susceptible to listeriosis, as oxygen availability may differ within the gastrointestinal tract.